2014
DOI: 10.1002/adsc.201400247
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Carbocyclization of Phenols with a Terminal Alkyne via an Intramolecular ipso‐Friedel–Crafts Alkenylation

Abstract: Abstract:We have developed a novel synthetic method to furnish spiroA C H T U N G T R E N N U N G [4.5]cyclohexadienones using an gold-catalyzed carbocyclization of phenols with a terminal alkyne via an intramolecular ipsoFriedel-Crafts alkenylation. Using 2-5 mol% of gold catalyst, 1 equiv. of methanesulfonic acid, and 1 equiv. of 2,6-di-tert-butylpyridine, a variety of spiroA C H T U N G T R E N N U N G [4.5]cyclohexadienone derivatives with an exocyclic olefin unit was obtained in good to excellent yields. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 57 publications
0
25
0
1
Order By: Relevance
“…在金催化 C-C 不饱和键氢-官能团化反应中除了 吲哚衍生物作为亲核试剂以外, 苯酚衍生物也能作为亲 核 试 剂 实 现 金 催 化 苯 酚 的 去 芳 构 化 反 应 . 2014 年 , Hamada 小组 [26] 报道了第一例金催化的分子内苯酚和炔 图式 13 基于金催化环化反应的(±)-strictamine 的形式全合成 Scheme 13 Formal total synthesis of (±)-strictamine based on a gold-catalyzed cyclization 图式 14 金催化 2-炔丙基-β-四氢咔唑的扩环和螺环化反应 Scheme 14 Gold-catalyzed ring expansion and spirocyclization of 2-propargyl-β-tetrahydrocarbolines 烃环化去芳构化反应, 生成有用的螺 [ [32] .…”
Section: 分子内反应unclassified
“…在金催化 C-C 不饱和键氢-官能团化反应中除了 吲哚衍生物作为亲核试剂以外, 苯酚衍生物也能作为亲 核 试 剂 实 现 金 催 化 苯 酚 的 去 芳 构 化 反 应 . 2014 年 , Hamada 小组 [26] 报道了第一例金催化的分子内苯酚和炔 图式 13 基于金催化环化反应的(±)-strictamine 的形式全合成 Scheme 13 Formal total synthesis of (±)-strictamine based on a gold-catalyzed cyclization 图式 14 金催化 2-炔丙基-β-四氢咔唑的扩环和螺环化反应 Scheme 14 Gold-catalyzed ring expansion and spirocyclization of 2-propargyl-β-tetrahydrocarbolines 烃环化去芳构化反应, 生成有用的螺 [ [32] .…”
Section: 分子内反应unclassified
“…[4] Along with the earlier studies on the dearomatization of indoles [5] and anilines, [6] recent seminal reports by the groups of Hamada, [7] You, [8] Buchwald, [9] Feringa, [10] and Tang [11] have demonstrated that several spirocyclic and fused ring scaffolds could be obtained by transition-metal-catalyzed dearomative cyclizationso f phenol-derived precursors in an intramolecular fashion by the formation of one CÀCb ond. Remarkably,t ransition-metal-catalyzed dearomatization reactions of phenols and naphthols have served as an extraordinarily potent tool for generating some three-dimensional structures which are either difficult or impossible to form by conventional means.…”
mentioning
confidence: 91%
“…Remarkably,t ransition-metal-catalyzed dearomatization reactions of phenols and naphthols have served as an extraordinarily potent tool for generating some three-dimensional structures which are either difficult or impossible to form by conventional means. [4] Along with the earlier studies on the dearomatization of indoles [5] and anilines, [6] recent seminal reports by the groups of Hamada, [7] You, [8] Buchwald, [9] Feringa, [10] and Tang [11] have demonstrated that several spirocyclic and fused ring scaffolds could be obtained by transition-metal-catalyzed dearomative cyclizationso f phenol-derived precursors in an intramolecular fashion by the formation of one CÀCb ond. Notwithstanding these excellent examples,t here is ac ompelling need to develop more economical intermolecular cyclization processes with simpler phenol substrates which do not require costly multistep syntheses.…”
mentioning
confidence: 91%
“…However, there are relatively few publications on the investigation of gold catalysis in dearomatization reactions compared to other transition metals such as palladium and iridium . In 2014, Hamada and co‐workers reported a gold‐catalyzed carbocyclization of phenols with a terminal alkyne, and then You's group also realized the dearomatization of naphthols with a terminal alkyne under similar conditions in 2016 (Scheme A) . Inspired by these findings, we proposed that the efficient dearomatization of phenols with a terminal allene catalyzed by Au(I) would be an ideal approach for preparing related spirocyclohexadienones (Scheme B).…”
Section: Introductionmentioning
confidence: 99%